Role of lipids in virus assembly - Jamil S Saad (Frontiers Research Topics, 2015)
RNA enveloped viruses comprise several families belonging to plus and minus strand RNA viruses, such as retroviruses, flavoviruses and orthomyxoviruses. Viruses utilize cellular lipids during critical steps of replication like entry, assembly and egress. Growing evidence indicate important roles for lipids and lipid nanodomains in virus assembly. This special topic covers key aspects of virus-membrane interactions during assembly and egress, especially those of retroviruses and Ebola virus (EBOV). Virus assembly and release involve specific and nonspecific interactions between viral proteins and membrane compartments. Retroviral Gag proteins assemble predominantly on the PM. Despite the great progress in identifying the factors that modulate retroviral Gag assembly on the PM, there are still gaps in our understanding of precise mechanisms of Gag-membrane interactions. Studies over the last two decades have focused on the mechanisms by which other retroviral Gag proteins interact with membranes during assembly. These include human immunodeficiency virus (HIV), Rous sarcoma virus (RSV), equine infectious anemia virus (EIAV), Mason-Pfizer monkey virus (M-PMV), murine leukemia virus (MLV), and human T-lymphotropic virus type (HTLV-1). Additionally, assembly of filoviruses such as EBOV also occurs on the inner leaflet of the PM. The articles published under this special topic highlight the latest understanding of the role of membrane lipids during virus assembly, egress and release.